SAS Method: Creating Equity and Adaptivity for Students' Linguistic Skills - Hartono Hartono; Abdur Rosid; Fathor Rozi; Siti Musyarrafah; Idayati Idayati (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
The aim of this research was to describe the application of the SAS (Synthetic Structural Analytical) method as an effort for equality and adaptivity towards the linguistic skills of early age students. This research used the type of Classroom Action Research. The subjects of this research were class B1 students at TPA (20 students). Data collection techniques use observation, interviews and (closed) tests. The data analysis technique used is analysis of the percentage test results for students' reading skill categories based on the results obtained on observation sheets taken during the learning process. The results prove that the SAS method is able to develop students' reading skills so that they are effective and successful in achieving quality and adaptivity later at the elementary school level. The increase in the percentage of students' reading skills was obtained from the five aspects (sensory, perceptual, schemata, thinking and affective) which encouraged them to develop their reading skills in a structured and synthetic analysis. This research specifically described the success of the SAS method which can not only be a technique for improving students' reading skills, but can also make